PENGARUH FAKTOR SOSIAL DAN EKONOMI PETERNAK TERHADAP PERTUMBUHAN USAHA PETERNAKAN AYAM BROLER DI KABUPATEN MAROS PROVINSI SULAWESI SELATAN (The effects of Social and Economic factors of Farmers on the Development of Broiler Farming in Maros Regency) - St. Rohani; M. Darwis (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2017)
Broiler poultry husbandry is the most favorite kind of husbandry business due to its high level of product demand. Maros is a region which is well known as one of the central areas of broiler meat production in South Sulawesi. The development of broiler poultry business managed by the locals breeders could have a signifcant impact towards an increase revenue of the breeders. But in reality, not many of the poultry broiler breeders could well developtheir own businesses, in fact some of them have not made any progress since its establishment. The aim this research was to analyze the the effects of social and economic factors of the breeders on the growth of the broiler poultry business. It was conducted from November to December 2015 by using primary and secondary data The population of the research was all the broiler breeders in the area, while the number of samples taken from the population was 79. The primary data obtained from interviews with farm owners using the questioners that have been prepared before hand and the secondary data were obtained from the website and the relevant institution. Data were analyzed using multiple linear regression analysis. The results of the study indicated that the social and economic factors of the broiler breeders, either partial or simultant, had a signifcant effect on the growth of the bussiness of broiler poultry husbandry.